Experimental Design Of Cardio –Toxidrome Of I.V Calcium Channel Blocker Overdose In Pigeon (Journal of Pharmaceutical Negative Results, 2023)
Study design and objectives: Goal; To evaluate and assess ,the effects of verapamil((CCB) overdose on systemic toxicity in awake pigeon by experimental demonstration the signs and symptoms of verapamil via determination of the variables cardio- respiratory in the pigeon as Prospective, experimental trial model compared to control .Method : 24 healthy domestic pigeons were used, the verapamil intravenously administered in the pigeon’s ulnar wing vein at 4 mg/kg . Heart rate (HR),, respiratory rate (fR), indirect systolic arterial pressure (SAP) were measured prior to verapamil iv administration in the awake pigeons state at baseline (resting 0- time) and at 5, 10 ,15 ,20 minutes interval later and toxic gastrointestinal manifestations were observed compared to control ( 2 pigeons). Results; the baseline cardio-respiratory variables in the pigeon , the heart rate ,systolic arterial pressure and respiratory rate were dropped to the mean ± SD HR, SAP, fR respectively, 84+/-10beats minute(-1), 66+/-12 mmHg, 17 ± 2 breaths minute(-1). The regurgitation and vomiting, watery green droppings as gastrointestinal toxic manifestations were clearly noticed along with dizziness or lightheadedness and sudden death prognosis as well ,compared control pigeon's recordings . Conclusion; In the awake pigeon ,verapamil was induced dropping up to 35% of baseline(time-0) of cardio-respiratory variables with hypotension at the moderate level is associated with disparate effects on systemic hemodynamics, and toxic gastrointestinal manifestations ,probably resulting from differential reflex autonomic activations , death prognosis due to cardiac arrest